The importance of dental care in patients with Amyotrophic Lateral Sclerosis (ALS): a literature review (Research, Society and Development, 2022)
Amyotrophic Lateral Sclerosis (ALS) can be understood as a severe, progressive, idiopathic neurodegenerative disease, which affects the motor system or neuroaxis motor neurons, promoting areflexia, fasciculation, amyotrophy and paresis, for example - directly influencing the performance of hygiene favorable oral health in this patient, who becomes dependent on the care of other people, usually a family member. From this, an exploratory, qualitative and bibliographic methodology was used in the Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO) databases. Thus, an advanced search methodology was used through Boolean descriptors, inserting complete articles, published between the years 2005 to 2022 in Portuguese, English and Spanish. Based on this, it was observed that patients with ALS are more likely to develop caries lesions, accumulation of biofilm and dental calculus, changes in collagen in the gingival tissue, phonetic changes, muscle weakness, changes in the temporomandibular joint, changes in mastication, swallowing and gingivitis, with special oral hygiene needs on the part of this patient's caregivers, where the dental surgeon should also be included in this sphere of care for this patient with Amyotrophic Lateral Sclerosis, and should be equipped with techniques and methods for each specific patient , closely monitoring the patient's entire previous history of oral hygiene, evaluating, correcting, preserving or modifying the current habits that caregivers already perform in this patient, ensuring adequate maintenance of oral hygiene and, consequently, systemic health for him, since the mouth is one of the main entry points for infections or new pathologies.